Pengaruh Bauran Pemasaran Syariah terhadap Keputusan KonsumenMembeli Produk pada Sentra Oleh-Oleh Makanan di Pasar Wisata Pekanbaru - Lisa Nurjanah; Julina Julina; Sitti Rahmah (Kutubkhanah, 2021)
This research is motivated to know is there any effect partially and simultaneously between the variables of the product ( product) , perception of price ( price perception ), where ( place ), promotion ( promotion ), HR / People ( people ), process ( process ), physical evidence ( physical evidence ), patience ( patience ), and promise ( promise ), towards consumer decisions to buy products at the food souvenir center at Pasar Wisata Pekanbaru. The type of research used is field research with quantitative research methods. The population and sample in this study were 96 consumers who bought products at the food souvenir center at the Pekanbaru Tourism Market. Data collection techniques in this research through observation, interviews, questionnaires, and documentation and research sites located in Pekanbaru, whereas in data processing using SPSS version 24.0 Based ha seals the research results as a whole variable product , price perception , place , promotion , people , process, physical evidence , patience , and promise an effect of partial and simultaneously to consumer decisions to buy products at the center of souvenirs food in Pekanbaru Travel Market.